CD146+ Umbilical Cord Mesenchymal Stem Cells Exhibit High Immunomodulatory Activity and Therapeutic Efficacy in Septic Mice - Zhang L; Zhang X; Liu Y; Zhang W; Wu CT; Wang L (Dove Medical Press, 2023)
Lin Zhang,1,2 Xiaoxu Zhang,1 Yubin Liu,2 Weiyuan Zhang,1 Chu-Tse Wu,2 Lisheng Wang1,3 1Laboratory of Molecular Diagnosis and Regenerative Medicine, the Affiliate Hospital of Qingdao University, Qingdao, People's Republic of China; 2Beijing Institute of Radiation Medicine, Beijing, People's Republic of China; 3Department of Rehabilitation Sciences, School of Nursing, Jilin University, Changchun, People's Republic of ChinaCorrespondence: Lisheng Wang, Laboratory of Molecular Diagnosis and Regenerative Medicine, the Affiliate Hospital of Qingdao University, Qingdao, 266000, People's Republic of China, Email lishengwang@qdu.edu.cnBackground: Several studies have shown that MSCs can significantly improve the survival of sepsis animals. CD146+ mesenchymal stem cells (MSCs) correlate with high therapeutic potency. However, their therapeutic effect on sepsis and detail mechanisms have not been explored.Methods: The effect of CD146±MSCs on differentiation of Treg, Th1, Th17 subsets was evaluated by flow cytometry. The effects of CD146±MSCs on RAW264.7 phagocytosis and LPS-stimulated polarization were studied using a co-culture protocol. Luminex bead array and RNA sequencing were employed to determine the mechanisms of MSCs on LPS-stimulated RAW264.7. The Arg1 protein was detected by Western blot. CD146±MSCs were injected into LPS-induced sepsis mice by tail vein. The therapeutic effect was assessed by organ HE staining, T-cell subsets, cytokine in plasma, peritoneal macrophages, infiltrating monocytes subpopulations.Results: In vitro, CD146+MSCs could significantly increase the proportion of Treg cells. Co-culture with CD146+MSCs increase the phagocytic rate of RAW264.7. CD146+MSCs regulate M2-type macrophages production more rapidly. The transcript profile differences between the CD146+MSCs and CD146-MSCs groups were clustered in arginine metabolism pathways. CD146+MSCs decreased NO production and increased ARG1 expression. CD146+MSCs secreted higher level of IL15,IFNγ, VEGF and lower level of IL1β, IL8 under LPS stimuli. In vivo, The level of IL10 at 24h and CXCL1, IFNγ at 12h in CD146+MSCs group was the highest. CD146+MSCs treatment enhances the phagocytic capacity of peritoneal macrophages. CD146+MSCs also increases the ratios of CD11b+Ly6Clo reparative monocytes and CD11b+Ly6Chi inflammatory monocytes until 24h.Conclusion: Compared with CD146-MSCs, CD146+MSCs can accelerate the end of the inflammatory response and have robust anti-inflammatory effects, by increasing the Treg cells, promoting macrophage phagocytosis, enhancing the reparative macrophage, secreting more VEGF, etc.Keywords: UC-CD146±MSCs, macrophages, sepsis, anti-inflammatory